Pembuatan Bioetanol Dari Nira Aren Secara Fermentasi Menggunakan Yeast Saccharomyces Cerevisiae Dengan Variasi Konsentrasi Inokulum Dan Waktu Fermentasi - Elia Simanjuntak; Chairul Chairul; Maria Peratenta Sembiring (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Bioethanol is one of the alternative energy source that can replace fossil energy sources. Bioethanol is biochemistry fluid from fermentation process of sugar by using microorganisms. One material which has potential as raw material for bioethanol production is a palm juice which is economically valuable products of the sugar plant. Palm juice is used as raw material for ethanol because it contains sugar which is large enough around 12.04%. This research aimed to produce bioethanol with various concentration of inoculum 10%, 12.5%, 15% and 17.5% and fermentation time 24, 48, 72 and 96 hours at pH optimum 5. The process of fermentation using Saccharomyces cerevisiae yeast. The sample analysed by using alcoholmeter. From the research results, obtained the highest ethanol concentration of 8% (v/v) at 17.5% inoculum concentration variation with fermentation time 72 hours.Keyword: Bioethanol, Fermentation, Palm Juice, Saccharomyces cerevisiae